2017
DOI: 10.1159/000485111
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion Tensor Imaging Investigation of Uncinate Fasciculus Anatomy in Healthy Controls: Description of a Subgenual Stem

Abstract: The uncinate fasciculus is the largest white matter association tract connecting the prefrontal cortex and the anteromedial temporal lobe. The traditional anatomical description outlines a temporal stem that hooks around the posterior insula, a subinsular body, and 2 prefrontal stems extending to the lateral orbital gyri and the frontopolar cortex. Recent imaging studies of the white matter tracts deep to the subgenual cingulate gyrus (Brodmann area 25: BA25) suggest the presence of white matter fibers extendi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 36 publications
0
23
0
Order By: Relevance
“…Anatomically, the uncinate fasciculus is a U-shaped, fanning white matter bundle with complex structure (Ebeling and von Cramon, 1992;Bhatia et al, 2012Bhatia et al, , 2017Bhatia et al, , 2018Riva-Posse et al, 2014;Vergani et al, 2016) and a number of termination points in the medial temporal lobes (Ebeling and von Cramon, 1992;Thiebaut de Schotten et al, 2012;Von Der Heide et al, 2013). It has only recently been visualized using Q-space imaging methods that model the U-shaped uncus and orbitofrontal cortex branching and turning patterns (Leng et al, 2016;Bhatia et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Anatomically, the uncinate fasciculus is a U-shaped, fanning white matter bundle with complex structure (Ebeling and von Cramon, 1992;Bhatia et al, 2012Bhatia et al, , 2017Bhatia et al, , 2018Riva-Posse et al, 2014;Vergani et al, 2016) and a number of termination points in the medial temporal lobes (Ebeling and von Cramon, 1992;Thiebaut de Schotten et al, 2012;Von Der Heide et al, 2013). It has only recently been visualized using Q-space imaging methods that model the U-shaped uncus and orbitofrontal cortex branching and turning patterns (Leng et al, 2016;Bhatia et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, a right UNC parameter demonstrated a moderate correlation with sensory sensitivity–auditory. The UNC not only connects the orbitofrontal cortex and temporal lobe anatomically, but also is considered the key pathway associated with episodic memory, language, and social emotional processing 43 , 44 . A recent meta-analysis of 25 DTI-based studies indicated that individuals with ASD showed decreased FA in the UNC, thus supporting the theory of specific underconnectivity in patients with ASD who show difficulty in social auditory information and language processing 45 .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have linked lower FA values in the left UF with negative symptoms in schizophrenia, and this pattern was not seen in patients with non-deficit schizophrenia [ 25 , 26 ]. Bahatia et al demonstrated a reduction in white matter integrity of the UF, which may translate to risk of mental disorders such as first-onset and chronic depression [ 9 ]. However, these studies are not equivocal because some researchers have reported an increase or no change in the FA values and indicate a small share of the bundle in the pathogenesis of schizophrenia [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…The UF is also known as a ‘hook-shaped’ fascicle connecting the prefrontal cortex and the anteromedial temporal lobe. The traditional anatomical description outlines a temporal stem that hooks around the posterior insula, a subinsular body, and two prefrontal stems that extend to the lateral orbital gyri and the frontopolar cortex [ 9 ]. The UF interconnects regions that support acoustic memory, visual information, and emotional responses [ 10 ].…”
Section: Introductionmentioning
confidence: 99%